Evaluation of Febrile Neutropenia in Hematologic Malignancy Patients - Müge ASLAN (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2014)
Introduction: Febrile neutropenia, developing in hematological cancer patients, is a common complication requiring hospitalization and resulting in death. It is assumed that it is caused by infection until its reason is clarified. Hence, it requires a multidisciplinary approach and treatment as a medical emergency. For these patient groups, most of whom are at high risk, death caused by infection is attempted to be minimized by continuously updating treatment approaches. This study aimed to determine clinical characteristics, risk factors, distribution and frequency variance of isolated pathogens and impact in mortality of hematological cancer patients with febrile neutropenia prospectively. Materials and Methods: In this study, 161 febrile neutropenia episodes of 99 patients with hematological cancer monitored between January 2012 and January 2013 in the Department of Hematology in the Hospital of our Medical Faculty were evaluated. Age, gender, underlying disease, chemotherapy regimens, hematologic and radiologic findings, antibacterial and fungal therapeutic regimens were recorded. Routine microbiological blood and urine cultures were performed. When necessitated, cultures from other sterile body sites were taken. Results: Mean age of the patients in the study group was 50.7 ± 15.9. Mean duration of hospitalization was 29.7 ± 14.9 days. Meanduration of neutropenia was 14.6 ± 5.7 days. In 21% of the evaluated episodes, microbiologically defined infection was found, where clinically defined infection was determined in 40% and fever of unknown origin was determined in 39%. A total of 47 isolates were isolated in total. When distribution of all isolated microorganisms, in all cultures was evaluated, 40% were grampositives, 47% were gram-negatives and 13% were fungi. The most frequently observed microorganisms were coagulase negative staphylococci with 31% and Escherichia coli with 22%. In blood cultures, 58% were gram-positives, 32% were gramnegatives and 10% were fungi. The most frequent febrile neutropenia treatment used in our center was carbapenem monotherapy. Mortality rate was 25.4%. Neutropenia duration and stage were the most important factors increasing mortality risk. Conclusion: Febrile neutropenia is a complication which may result in mortality in patients with hematological cancer. In order to define treatment models, each center is supposed to determine its center’s microorganism spectrum and antibiotic resistance profiles periodically.